INTERPRETASI KEDALAMAN DAN KETEBALAN LAPISAN BATUBARA DENGAN MENGGUNAKAN METODE WELL LOGGING DI PT LAMINDO INTER MULTIKON SITE BUNYU - Sunarti, Sunarti; Supriyanto, Supriyanto; Djayus, Djayus (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2020)
The purpose of this study was to determine the depth and thickness of coal seams based on gamma ray log and log density. Interpretation of DPG01 drill point at a depth of 45.15 - 58.65 m there is coal with a thickness of 13.5 m, at a DPG04 drill point depth of 30.45 - 43.40 m there is coal with a thickness of 12.95 m, DPE04 drill point a depth of 23.00 - 36.10 m there is coal A with a thickness of 13.1 m, at depth 86.20 - 96.78 m there is coal B with a thickness of 10.58 m, DPE06 drill point depth 34.57 - 44.15 m there is coal A with a thickness of 9.58 m, at a depth of 86.15 - 92.33 m there is coal B with a thickness of 6.18 m, at 100.24 - 105.05 m there is coal C with a thickness of 4.81 m and a drill point DPE07 depth of 49.74 - 65.20 m there is coal A with a thickness of 15.46 m. The results of these interpretations produce an average on each coal seam. In seam A has an average thickness of 12.91 m, seam B has an average thickness of 8.38 m and seam C has a thickness of 4.81 m.